The Distribution in Biogeographic Region of Rare Plant Genus Tacca (Dioscoreaceae) in Thailand for Conservation: doi: 10.14456/mijet.2020.6 - Niamngon, Tawanon; Seansouk, Surapon; Seansouk, Piyaporn (Engineering Access, 2020)
The genus Tacca (Dioscoreaceae) is used as a medicinal plant with medicinal properties, outstanding in the matter of tonic treat rash, treat inflammation in both inside and outside the body, including hepatitis, dysentery and diarrhea. In Thailand, there are five species, namely T. Chantrieri Andre, T. integrifolia Ker Gawl., T. leontopetaloides (L.) Kuntze, T. palmata Blume and T. plantaginea (Hance) Drenth, distributed to cover the biogeographical region in seven regions, which are North, Northeast, East, Southwest, Central, South-East and South of Thailand. The biogeographic region of T. chantrieri Andre is distributed cover seven regions, which is 0-1,500 meters above sea level. While, the other three species; T. integrifolia Ker, Gawl. T. leontopetaloides (L.) Kuntze and T. palmata Blume; are distributed in some areas of the geographic regions, such as North, South-East and South, at an altitude of 0-1,200 meters above sea level. And one species, T. plantaginea (Hance) Drenth, is a rare plant, distributed at altitude of 100-800 meters above sea level with covered three biogeographic regions including the Northeast, South-West and Central. The biogeographic region map of rare plant genus Tacca species in Thailand for conservation is provided.